Category: Science > Math
Asked by: redcapelliragazo-ga
List Price: $7.00
21 Nov 2006 17:09 PST
Expires: 21 Dec 2006 17:09 PST
Question ID: 784657
How do you find the inverse to F(x)=(-7x + 3)/(-9x - 9 )?
Re: Calc: Inverse
Answered By: livioflores-ga on 22 Nov 2006 00:11 PST
Hi!! You need to isolate x from the equation: y = (-7x + 3)/(-9x - 9) ==> y = (-7x + 3)/(-9x - 9) ==> y*(-9x - 9) = -7x + 3 ==> -9xy - 9y + 7x = 3 ==> -9xy + 7x = 3 + 9y ==> x*(-9y + 7) = 3 + 9y ==> x = (3 + 9y)/(-9y + 7) From the above result we have that: G(y) = (3 + 9y)/(-9y + 7) is the inverse of the function F. Note that F is undefined at x=1 and G is undefined at y=7/9. See for references the following pages: "Finding the Inverse of a Function: More Examples" http://www.purplemath.com/modules/invrsfcn5.htm "Find Inverse Function (1) - Tutorial": http://www.analyzemath.com/inversefunction/Tutorials.html "Find Inverse Function (2) - Tutorial": http://www.analyzemath.com/inversefunction/Tutorials2.html Search strategy: "inverse function" find I hope this helps you. Feel free to request for a clarification if you need it. Regards, livioflores-ga
rated this answer:
Thanks sooo much. :-)
|There are no comments at this time.|
If you feel that you have found inappropriate content, please let us know by emailing us at email@example.com with the question ID listed above. Thank you.
|Search Google Answers for|